Early sexual debut and associated factors among students in Ethiopia: a systematic review and meta-analysis - Birye Dessalegn Mekonnen (SAGE Publishing, 2020)
Students with early sexual debut are exposed to risky sexual behaviours. For effective intervention of early sexual debut and its consequences, determination of its magnitude and identifications of associated factors is important. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence and its associated factors of early sexual debut among students in Ethiopia. Articles were identified through databases such as PubMed, Global Health, HINARI, Google advance search, Scopus, and EMBASE from March 10th to April 3rd. The data was extracted using a standardized data extraction form and exported to STATA 11 for analysis. The overall pooled prevalence of early sexual debut among students was estimated using a random-effects meta-analysis. Presence of association was determined using an odds ratio with a corresponding 95% CI. A total of 9 studies with 4,217 participants were involved in this meta-analysis. The estimated pooled prevalence of early sexual debut among students in Ethiopia was 27.53% (95% CI: 20.52, 34.54). Being female (OR: 3.64, 95% CI: 1.67, 5.61), watching pornography (OR: 3.8, 95% CI: 2.10, 5.50) and having boyfriend or girlfriend (OR: 2.72, 95% CI: 1.24, 5.96) were found to be risk factors for early sexual debut. More than one fourth of students practiced early sexual debut. The finding suggests the need of strengthening prevention strategies, effective intervention, and programs to reduce early sexual debut and its consequences in educational institutions. Furthermore, special attention should be given to female students and students who watch pornography.